A interferência da fala na escrita de alunos de 8ª série de uma escola pública: uma perspectiva conexionista - Veçossi, Cristiano Egger (2010)
The present work has as main target to scrutinize errors of writing which motivations have phonetic/phonologic foundations. In order to do so, we take into consideration 35 texts, deriving of 27 pupils from two groups of the 8th grade from a state public school of the city of Santa Maria RS. For the data analysis we essentially apply the classification proposed by Zorzi (1998) which was adapted. In this manner, from the nine categories considered in this study, only one of them includes errors motivated by issues of the own orthographic system of Brazilian Portuguese, while the others contain phonetic/phonological aspects. Therefore, to each considered category, in a first moment, we try to explain in a phonological basis the data they contain. We also make comparisons with findings of other studies dealing with the relationship Phonology/Orthography. Inserted in a connectionist perspective, we present explanations for some of the occurrences found in the data. Finally, by the means of connectionist presuppositions, we advocate a possible change in the phonological system of the learner after the acquisition of writing. In this light, so to formalize such process, we present a Connectionist Optimality Theory analysis, focusing, especially, the acquisition of the lateral liquid in coda position.